Sports violence - Sharp, Anne Wallace (Detroit Gale Cengage Learning, 2011)
"The books in this series objectively and thoughtfully explore topics of political, social, cultural, economic, moral, historical, or environmental importance"--Provided by publisher.
"Lucent books, a part of Gale, Cengage Learning."--Title page.
Includes bibliographical references and index.
Keywords: Violence in sports; Aggressiveness